Uruguay, regionalism, regional integration: Partido nacional, neoherrerismo and regional disengagement as strategy - López Burian, Camilo; Hernández Nilson, Diego (Faculdade de Ciências e Letras - Unesp - Araraquara., 2021)
In 2020, a right coalitional government leaded by the National Party started in Uruguay, after 15 years of left governments. There are signs that show the beginning of a reorientation of foreign policy towards greater trade openness and attracting investment. As a counterpart, there seems to be a loss of the relative importance of the region in Uruguayan foreign policy, which includes demands for the opening up and flexibilitation of the Mercosur and a repositioning against regionalism. This change promoted by the new government may be counterintuitive in relation to the regional vocation traditionally attributed by literature to the National Party. However, through the analysis of a census and interviews with legislators, the article shows that in the last decade party preferences have already outlined this relegation of the region. In this way, we argue that a pragmatic, realistic and deeply liberal “neoherrerismo” is emerging in the National Party, as a predominant tendency in the international vision of the government.